C1‐continuous time integration based on cubic Hermite interpolation. Issue 1 (25th October 2016) - Mergel, Janine C.; Sauer, Roger A.; Ober‐Blöbaum, Sina
Abstract: We discuss a C 1 ‐continuous time integration method based on piecewise cubic Hermite approximation. This method, denoted as p2‐scheme, belongs to a class of one‐step integration methods derived recently [1]. It exhibits a convergence rate of order four and shows properties similar to variational integrators, such as an excellent long‐term energy preservation. (© 2016 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)